Quantum correlations in the radiative recombination into excited state of highly charged heavy ions. (August 2015) - Maiorova, A V; Tashenov, S; Surzhykov, A; Shabaev, V M; Stöhlker, T
Synopsis: We consider the radiative recombination of a free electron into the excited 2 p 3 /2 state of heavy H-like ion with the subsequent decay into the ground 1 s 1/2 state. Quantum correlations between two photons emitted in the process are studied.